(untitled) (Global Journal of Human-Social Science, 2012)
Title Rural development in a fast developing African society The Case of Mauritius Societies that are called modern are those where the states have encouraged a more holistic approach to development as both the urban and rural areas have been given much attention Most of the African countries face the difficulties to go for a balanced development program mainly because of financial problem but also because of lack of commitment on the part of the state stakeholders to develop design and implement appropriate policies for rural development The challenge for most developing societies is to make judicious useof available scarce resources to cause development and modernity that satisfies all the inhabitants In this paper the case of Mauritius a fast developing African society will be considered The main objectives of the paper are to I To take stock of the factors that have been taken by the Mauritius state since its independence to cause rural development and II To discuss whetherMauritius is a success story regarding rural development For the sake of this study use of both primary and secondary data has been made Books government documents information received from the Chief Regional Development Officer and Citizens Advice Bureau officers and observation have proved to be very useful in writing this paper The principal finding shows that Mauritius has resorted to the appropriate policies and the necessary implementation in achieving success in its rural development However the state needs to constantly review its policies and go for good governance to cope with new challenges so that the rural inhabitants are not left outside the mainstream of development